Superhelicenes in the gas phase: experimental and computational evidence of stable radical cation dimers - Kinzelmann, Marina; Reger, David; Warmbrunn, Vera; Lungerich, Dominik; Jux, Norbert; Drewello, Thomas (Chemical Communications, 2023)
Electrospray-ionization mass spectrometry (ESI-MS) readily produces stable radical cation pi-dimers of the superhelicenes. Energy-resolved collision experiments reveal the dissociation of the dicationic dimer into two singly charged superhelicenes. DFT calculations indicate that open-shell dications composed of two radical cations are thermochemically more attractive than the closed-shell dimer formed by a doubly charged and a neutral superhelicene.
CRIS-Team WoS Importer:2023-05-12